Intergenerational transmission of economic self-sufficiency: insights from the comparative analysis - Tosun, Jale; Pauknerová, Daniela; Kittel, Bernhard (Intergenerational transmission and economic self-sufficiency, 2021)
In this chapter, we compare the findings reported by the authors of chapters 4 to 14 and offer some general reflections and conclusions. Our overall goal is to provide answers to the research questions posed in chapter 1 and to assess the conceptual model developed in chapter 2. To this end, we proceed as follows. First, we outline the dimensions of the comparative discussion of the findings as derived from our theoretical model. Second, we offer a structured overview of the findings reported in each case study and compare these to each other. Then we turn to answering the research questions that guided this study.
Gesehen am 19.06.2023